Presentation, management, and outcomes of norovirus in adult and pediatric solid organ and hematopoietic stem cell transplant recipients: A multicenter, retrospective study - Callegari, Michelle; Danziger‐Isakov, Lara A.; Rose, Anne; Kaul, Daniel; Shaffer, Kelly; Chong, Pearlie P.; Florescu, Diana; German, Kaci; Avery, Robin; Nguyen, M. Hong; Wildfeuer, Brett; Michaels, Marian G.; et al. (Transplant Infectious Disease, 2024)
Background: Norovirus (NoV) can cause chronic relapsing and remitting diarrhea in immunocompromised patients. Few multicenter studies have described the clinical course, outcomes, and complications of chronic NoV in transplant recipients.

Noroviral diarrhea in solid organ transplant recipients: An analysis of interventions and outcomes - Nair, Sashi N.; Bhaskaran, Archana; Chandorkar, Aditya; Fontana, Lauren; Obeid, Karam M. (Clinical Transplantation, 2023)
Introduction Noroviral infection can lead to chronic diarrhea in solid organ transplant (SOT) recipients with significant morbidity and mortality. Existing literature has described a wide spectrum of illness and has not come to a consensus on the optimal management of this condition. Methods We undertook a retrospective review of all adult SOT recipients between 1/1/2018 and 12/31/2020 who were diagnosed with their first episode of noroviral diarrhea (NVD). Demographic, clinical interventions, and outcomes within 6 months of diagnosis were recorded. Patients’ outcomes were classified as either resolved, improved or persistent at 6 months. Results Seventy‐nine SOT recipients were included. Thirty‐eight patients (48%) had chronic diarrhea at baseline (CDB). Thirty‐two patients (40%) received nitazoxanide, 28 patients (35%) had their immunosuppression adjusted and seven patients (9%) received intravenous immunoglobulin. Diarrhea improved or resolved in 68 patients (85%). Improvement or resolution of diarrhea was observed in 98% of those who did not have history of chronic diarrhea versus 74% in those who did (p = .002). NVD improved in all 12 patients who had mycophenolate discontinued, although this was not statistically significant (p = .131). Conclusion CDB was associated with worse outcomes regardless of intervention. A low threshold to test for NVD in SOT recipients with chronic diarrhea is prudent to prevent delayed diagnosis.

How I approach diarrhea in hematological transplant patients: A practical tool - Castillo Almeida, Natalia E.; Cichon, Catherine J.; Gomez, Carlos A. (Transplant Infectious Disease, 2023)
Diarrhea in hematopoietic stem-cell transplantation (HSCT) remains a multifactorial challenge that demands a nuanced diagnostic approach. The causes of infectious diarrhea in HSCT recipients are diverse and influenced by patient-specific risk factors, the post-transplant timeline, and local epidemiology. During the past decade, our understanding of diarrhea in HSCT has witnessed a transformative shift through the incorporation of gastrointestinal (GI) multiplex polymerase chain reaction (PCR) panels. However, the judicious application of these panels is imperative to avoid overtesting and prevent adverse outcomes. The challenge lies in distinguishing between the diverse causes of diarrhea, ascertaining the clinical significance of detected pathogens, and navigating the diagnostic uncertainty presented by several non-infectious conditions such as mucositis, intestinal dysbiosis, and acute graft-versus-host disease (aGvHD), all of which mimic infection. This review examines the landscape of infectious diarrhea in the HSCT population, encompassing both established (e.g., Cytomegalovirus, Clostridioides difficile, and norovirus) and emerging pathogens (e.g., sapoviruses, astroviruses). We propose a multifaceted diagnostic algorithm that combines clinical assessment, risk stratification, and tailored utilization of molecular platforms. While multiplex GI panels present invaluable opportunities for rapid and comprehensive pathogen detection, their judicious use is pivotal in preserving diagnostic stewardship. Customization of diagnostic algorithms tailored to local epidemiology ensures optimal patient care and resource utilization.
Keywords: CMV; Clostridioides difficile; acute graft-versus-host disease (aGvHD); diarrhea; gastrointestinal panel; hematopoietic stem-cell transplantation; multiplex; syndromic

Nitazoxanide treatment for norovirus infection in solid organ transplant recipients - Hedvat, Jessica; Salerno, David M.; Kovac, Danielle; Scheffert, Jenna L.; Corbo, Heather; Chen, Justin K.; Choe, Jason Y.; Jennings, Douglas L.; Anamisis, Anastasia; Liu, Esther C.; Lee, Jennifer H.; Shertel, Tara; et al. (Clinical Transplantation, 2022)

Norovirus in Cancer Patients: A Review - Kondapi, Divya Samantha; Ramani, Sasirekha; Estes, Mary K; Atmar, Robert L; Okhuysen, Pablo C (Open Forum Infectious Diseases, 2021)
Abstract Norovirus (NoV) is the leading cause of viral-related diarrhea in cancer patients, in whom it can be chronic, contributing to decreased quality of life, interruption of cancer care, malnutrition, and altered mucosal barrier function. Immunosuppressed cancer patients shed NoV for longer periods of time than immunocompetent hosts, favoring quasispecies development and emergence of novel NoV variants. While nucleic acid amplification tests (NAATs) for NoV diagnosis have revolutionized our understanding of NoV burden of disease, not all NAATs provide information on viral load or infecting genotype. There is currently no effective antiviral or vaccine for chronic NoV infections. Screening for inhibitors of NoV replication in intestinal organoid culture models and creation of NoV-specific adoptive T cells are promising new strategies to develop treatments for chronic NoV in immunosuppressed patients. Herein we summarize data on the epidemiology, clinical manifestations, diagnostic challenges, and treatment of NoV infection in patients with cancer.

Fecal microbiota transplantation for norovirus infection: a clinical and microbiological success - Barberio, Brigida; Massimi, Davide; Bonfante, Luciana; Facchin, Sonia; Calò, Lorenzo; Trevenzoli, Marco; Savarino, Edoardo Vincenzo; Cattelan, Anna Maria (Therapeutic Advances in Gastroenterology, 2020)

Mutagenesis in Norovirus in Response to Favipiravir Treatment - Ruis, Christopher; Brown, Li-An K.; Roy, Sunando; Atkinson, Claire; Williams, Rachel; Burns, Siobhan O.; Yara-Romero, Erika; Jacobs, Michael; Goldstein, Richard; Breuer, Judith; Lowe, David M. (New England Journal of Medicine, 2018)
Favipiravir for Chronic Norovirus Infection Norovirus may cause chronic diarrhea, especially in immunosuppressed patients. There is no established treatment. In this case report, favipiravir is shown to have some evidence of activity and to induce some selective pressure on the virus.

Norovirus Gastroenteritis in Immunocompromised Patients - Bok, Karin; Green, Kim Y. (The New England journal of medicine, 2013)